EXTENDED BELIEF AND EXTENDED KNOWLEDGE. - Wikforss, Åsa (Philosophical Issues, 2014)
The article discusses extended belief and extended knowledge. It argues that the fundamental problem arises at the level of belief instead of the level of knowledge by denying the principled possibility of extended beliefs. It also considers authors D. Chalmers and A. Clark's suggestions regarding the distinctive role of belief in folk psychology.